Theoretical insights about CZTSSe chalcogenides alloys for photovoltaic applications - Casierra Minda, Jordan Joel (2024)
The present work focuses on the theoretical study of CZTSSe type alloys for photo voltaic applications. CZTSSe alloys possess excellent optical and electronic properties, which makes them promising candidates for this application. The studied systems are Ag2ZnSnSe4, Cu2BaSnS4, Cu2CdSnS4, Cu2ZnGeS4, Cu2ZnSnS4, Cu2ZnSnSe4 y CZTSSe. For this, we used the Vienna Ab initio Simulation Package, a program for simulating the electronic and structural properties of materials. First, the different bulk modulus were calculated, important for understanding the mechanical resistance of the system. Conse quently, the enthalpy of mixing and formation were obtained, allowing to know the stability of the compound, which compound is more favorable to form. Subsequently, band struc ture calculations helped us to identify which orbitals contribute the most to the valence and conduction bands, thus knowing the atom to add to tune the band gap. On the other hand, the calculated values of the band gap confirmed that these were semiconductors with potential for photovoltaic applications, since it was in the 1.1-1.8 eV range. This band gap range is ideal because it also permits good absorption of sunlight and efficient conversion of that light into electrical energy. It was also analyzed how these properties change by varying the composition S and Se in Cu2ZnSn(SxSe1−x) (CZTSSe), using values of 0.25, 0.50, 0.375, 0.625, and 0.75. Finally, it was determined that the best composition of CZTSSe alloys for photovoltaic applications is S0.75Se0.25 due to its good band gap value (1.55 eV), formation enthalpy (-0.44579 eV/atom), and mechanical resistance (65.628 GPa).